Empirical Testing of Real Option-Pricing Models. - Quigg, Laura (Journal of Finance, 1993)
This research is the first to examine the empirical predictions of a real option-pricing model using a large sample of market prices. The author finds empirical support for a model that incorporates the option to wait to develop land. The option model has explanatory power for predicting transactions prices over and above the intrinsic value. Market prices reflect a premium for the option to wait to invest that has a mean value of 6 percent in the sample. The author also estimates implied standard deviations for individual commercial property prices ranging from 18 to 28 percent per year.